2022
DOI: 10.1038/s41598-022-18165-0
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl hydroxylase 2 mediated collagen post-translational modifications and functional outcomes

Abstract: Lysyl hydroxylase 2 (LH2) is a member of LH family that catalyzes the hydroxylation of lysine (Lys) residues on collagen, and this particular isozyme has been implicated in various diseases. While its function as a telopeptidyl LH is generally accepted, several fundamental questions remain unanswered: 1. Does LH2 catalyze the hydroxylation of all telopeptidyl Lys residues of collagen? 2. Is LH2 involved in the helical Lys hydroxylation? 3. What are the functional consequences when LH2 is completely absent? To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Importantly, when telopeptidyl Lys hydroxylation is deficient, no Hyl ald -derived cross-links are formed causing collagen to become highly soluble and significantly more susceptible to enzymatic degradation. 27 These data provide clear evidence that driving collagen cross-linking toward the LH2-mediated, Hyl ald -derived pathway makes collagen insoluble and more resistant to enzymatic degradation. This finding may explain, at least partially, why LH2 overexpression seen in various cancer types promotes formation of a stiffened collagen matrix.…”
Section: Lysyl Hydroxylase 2: a Key Enzyme For Collagen Stability And...mentioning
confidence: 76%
See 4 more Smart Citations
“…Importantly, when telopeptidyl Lys hydroxylation is deficient, no Hyl ald -derived cross-links are formed causing collagen to become highly soluble and significantly more susceptible to enzymatic degradation. 27 These data provide clear evidence that driving collagen cross-linking toward the LH2-mediated, Hyl ald -derived pathway makes collagen insoluble and more resistant to enzymatic degradation. This finding may explain, at least partially, why LH2 overexpression seen in various cancer types promotes formation of a stiffened collagen matrix.…”
Section: Lysyl Hydroxylase 2: a Key Enzyme For Collagen Stability And...mentioning
confidence: 76%
“…The function of LH2 as a telopeptidyl LH was first proposed by Uzawa et al 35 and was further confirmed in part by Mercer et al, 86 van der Slot et al, 36,89 and Pornprasertsuk et al 37,91 Since LH2-knockout mice die at an early embryonic stage (E10.5), 92 we generated LH2-deficient cells and characterized the molecular phenotypes. 27 The results demonstrated that LH2 is responsible for both N-and C-telopeptidyl Lys hydroxylation of α1 and α2 chains of type I collagen, and showed that other LH family members cannot compensate for this function. Importantly, when telopeptidyl Lys hydroxylation is deficient, no Hyl ald -derived cross-links are formed causing collagen to become highly soluble and significantly more susceptible to enzymatic degradation.…”
Section: Lysyl Hydroxylase 2: a Key Enzyme For Collagen Stability And...mentioning
confidence: 93%
See 3 more Smart Citations